PENGARUH KEMAMPUAN SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN BARANG MILIK NEGARA - Kurniawan, Kurniawan; Saiful, Saiful; Midiastuti, Pratana Puspa (JURNAL FAIRNESS, 2016)
The purpose of this research is to analyze the influence of human resources capacity and the utilization of information technology toward the quality of state property report. This research was conducted on units under the KPPN Bengkulu authority.The populations of this research were the operators of state property reports in the units under the KPPN Bengkulu authority whose have more than 2 years working experiences. The variables of this research are the human resources capacity and the utilization of information technology as the independent variables and the dependent variable is the quality of state property report (Y). The data are collected from the questionnaire filled by 121 operators of the state property report. The data analysis method of this research was multiple linear regressions.The results show that the human resources capacity and the utilization of information technology have the positive influence toward the quality of state property report. The implication of this research toward the units was the units under the KPPN Bengkulu authority have to manage the human resources and utilize the state property.